Omnipresence of the mobile phone: contributions towards a reflection. (Journal of the Sociology and Theory of Religion, 2019)
The growing use of the mobile phone shows that this is socially widely accepted communication medium. Its use is intensive and multifunctional and begins at early stages. In fact, the generalized habit of having a mobile phone in their lives transforms this technology into a vital element and has significant impact on people’s behaviour.It must be emphasised that several entities recommend the use of mobile phones as a pedagogic tool within the classroom. More empirical studies are being carried out in relation to the use of mobile phones, especially among young people, in formal and informal contexts.Therefore, this contribution aims at promoting thought about the ‘social experience’ of using the mobile phone in order to establish an adequate and moderate attitude in daily life.
Keywords: mobile phones, use